Frizzled receptors in melanomagenesis: From molecular interactions to target identification - Umar, Sheikh A.; Dong, Bo; Nihal, Minakshi; Chang, Hao (Frontiers in Oncology, 2022)
Frizzled (FZD) proteins are receptors for the WNT family ligands. Inherited human diseases and genetic experiments using knockout mice have revealed a central role of FZDs in multiple aspects of embryonic development and tissue homeostasis. Misregulated FZD signaling has also been found in many cancers. Recent studies on three out of the ten mammalian FZDs in melanoma have shown that they promote tumor cell proliferation and invasion, via the activation of the canonical WNT/β-catenin or non-canonical PCP signaling pathway. In this concise review, we summarize our current knowledge of individual FZDs in melanoma, discuss the involvement of both the canonical and non-canonical pathways, and describe ongoing efforts to target the FZD receptors for melanoma treatment.